Pengembangan Media Pembelajaran Berbasis Scratch pada Materi Perkalian Sekolah Dasar - Rila Yulastari; Refiona Andika; Fadila Suciana; Yullys Helsa (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
Elementary School. The method used is Research and Development (R&D) with the ADDIE development model consisting of five stages, namely Analysis, Design, Development, Implementation, and Evaluation. Implementation was carried out with a limited trial. The subjects of the limited trial were fourth-grade students of SDN 48 Payakumbuh. The validity of the media was tested by material experts, language experts, and media experts with percentage results of 82%, 100%, and 86%, respectively, all of which are included in the "very valid" category. The practicality of the media based on teacher responses reached 90% and from students 94.27%, which indicates that this media is "very practical". The activeness after using Scratch with a percentage of 90.31% with the "very active" category is higher than the percentage before using Scratch even though the intent is the same. Meanwhile, in mastery of understanding the concept of multiplication, the media was tested through summative assessment results with an average score of 93.33%, included in the "very good" category. Based on these findings, it can be concluded that the developed Scratch media is valid, practical, and increases the activeness and understanding of multiplication concepts. It is also valid for use in mathematics learning in fourth-grade elementary school